Modification of in situ Biofilm Formation on Titanium by a Hydroxyapatite Nanoparticle-Based Solution - Nobre, Cíntia M. G.; Pütz, Norbert; König, Belinda; Rupf, Stefan; Hannig, Matthias (Frontiers in Bioengineering and Biotechnology, 2020)
Oral biofilms play an essential role on peri-implant disease development. Synthetic hydroxyapatite nanoparticles (nHAP) are a bioinspired material that has structural and functional similarities to dental enamel apatite and may provide preventive properties against biofilm formation. This study aimed to investigate the effects of an experimental nHAP solution on biofilm formation on polished and non-polished titanium under oral conditions. Five volunteers carried maxillary splints with non-polished and polished titanium and followed a 48h rinsing protocol with the proposed nHAP solution, and with chlorhexidine 0.2% (CHX) and water, as controls. Samples were analyzed by fluorescence microscopy (FM), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). FM showed a significant reduction of biofilms on polished samples treated with nHAP (p=0.0485) compared with water, without differences between nHAP and CHX (p>0.9999). Analyzing biofilm viability, polished samples rinsed with nHAP showed significantly fewer dead bacteria than CHX (p=0.0079), but there was no significant difference in viability between polished samples rinsed with water and nHAP (p=0.9268). A significantly higher biofilm coverage was observed on the non-polished surfaces compared to the polished surfaces when nHAP was applied (p=0.0317). This difference between polished and non-polished surfaces was not significant when water (p=0.1587) or CHX (p=0.3413) rinsing were applied. SEM and TEM analysis supported the FM findings, that polished samples rinsed with nHAP presented fewer biofilm coverage compared to samples rinsed with water. In conclusion, the nHAP solution reduced the biofilm formation on polished Ti surfaces without altering bacterial viability, providing a novel approach for the management of biofilm formation on biomaterials.